FMCR 2020
DOI: 10.47746/fmcr.2020.1209
|View full text |Cite
|
Sign up to set email alerts
|

Osseous Metaplasia in a Rectal Inflammatory Polyp in an Adolescent Patient: A Case Report and Review of the Literature

Abstract: Osseous metaplasia/heterotopic bone formation is a well-known phenomenon encountered in various neoplastic and non-neoplastic conditions. Osseous metaplasia in colorectal polyps is extremely rare. We report a case of osseous metaplasia in a rectal inflammatory polyp in a 17-year-old man with a longstanding history of painless rectal bleeding. The patient was referred to our facility for evaluation of a four-month history of painless rectal bleeding, as well as rectal prolapse and episodes of fecal urgency. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Around 21 previous cases have reported osseous metaplasia. The patients present clinically with a history of painless rectal bleeding with or without prolapsed rectal mass [1][2][3][4][5][6]. Further, the age variation of osseous metaplasia cases is between nine and 39 years, with a few elderly cases above 70 years old [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Around 21 previous cases have reported osseous metaplasia. The patients present clinically with a history of painless rectal bleeding with or without prolapsed rectal mass [1][2][3][4][5][6]. Further, the age variation of osseous metaplasia cases is between nine and 39 years, with a few elderly cases above 70 years old [5].…”
Section: Discussionmentioning
confidence: 99%
“…The patients present clinically with a history of painless rectal bleeding with or without prolapsed rectal mass [1][2][3][4][5][6]. Further, the age variation of osseous metaplasia cases is between nine and 39 years, with a few elderly cases above 70 years old [5]. Moreover, the size of rectal polyps varies between 8 and 12 mm, with a male predominance [1][2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study published in 2003; Kawai et al (25) transferred the human BMP-2 gene to the skeletal muscle of rats by cutaneous electroporation and observed the formation of ectopic bone consisting of active osteoblasts and osteoclasts in all rats. Wood et al (5) presented a case of inflammatory rectal polyp with osseous metaplasia in a 17-year-old patient in their recent article and suggested that this may be a distinctive disease entity. We share the same perspective with them.…”
Section: Discussionmentioning
confidence: 99%
“…Very few cases have been reported, especially in the pediatric population. Although its pathophysiology is not known clearly, there are several theories suggested (5). In this case report, we presented a case of bone formation in a rectal inflammatory polyp presenting with rectal bleeding in a 7-year-old girl.…”
Section: Introductionmentioning
confidence: 95%